Refugees' and Irregular Migrants' Self-Selection into Europe: Who Migrates Where? - Cevat Giray Aksoy; Panu Poutvaara (Institute of Labor Economics (IZA), 2019)
We analyze self-selection of refugees and irregular migrants and test our theory in the context of the European refugee crisis. Using unique datasets from the International Organization for Migration and Gallup World Polls, we provide the first large-scale evidence on reasons to emigrate, and the self-selection and sorting of refugees and irregular migrants. Refugees and female irregular migrants are positively self-selected with respect to human capital, while male irregular migrants are negatively self-selected. These patterns are similar when analyzing individually stated main reason to emigrate, country-level conflict intensity, and sub-regional conflict intensity. Migrants respond to economic incentives and border policies.
Keywords: F22; J15; J16; J24; O15; 330; international migration; refugees; irregular migrants; self-selection; human capital; gender differences in migration